Measurement of Natural and Artifical Radionuclides of Stevia Rebaudiana Bertoni Extract - Salam, M Abdus; Ahmed, Kabir; Morshed, AJM; Hossain, MK; Chowdhury, S Yesmin; Chowdhury, Md Musa (Bangladesh Journal of Scientific and Industrial Research, 2010)
Present study was carried out to measure the natural and artificial radionuclides of two different extract of Stevia Rebandiana Bertoni and a standard sugar solution. Factor affecting low-background Germanium Spectroscopy with HPGE Detectors, which is sensitive to all Gamma energies have been used for the measurement of natural and artifical radionuclides in stevia extracts and sugar solution. By analyzing two different types of Stevia extract samples and standard sugar solution sample, no significant presence of natural radionuclides were observed compared with background count. We also didn't find any artificial radionuclides in these three samples. So based on above observation we conclude that the leaves of Stevia Rebaudiana Bertoni extract is very safe to use as substitute of sugar as sweetener in foods and beverages for diabetics and obese people due to their potent sweetener stevioside and free of artifical radionuclides. Key Words: Natural radionuclides; Artificial radionuclides; Stevia extract; Sweetener; Food additives DOI: 10.3329/bjsir.v44i4.4600 Bangladesh J. Sci. Ind. Res. 44(4), 467-472, 2009